PELAKSANAAN PELAYANAN ADMINISTRASI DI SUBBAGIAN AKADEMIK FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS SEBELAS MARET - Desi Rahmawati; Tri Murwaningsih; Anton Subarno (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2021)
AbstractImplementation of Administrative Services in the Academic Subsection at the Faculty of Teacher Training and Education Sebelas Maret University. This research aims to find the implementation of administrative service, obstacles, and efforts to overcome the obstacles on implementations of administrative service. This research uses descriptive qualitative with a study case approach. The result shows: 1) The implementation of administrative service in Academic Subsection of the Faculty of Teacher Training and Education Sebelas Maret University are: services according to existing procedures, service has a certain period of time, services products vary, service facilities and infrastructure are quite adequate, basic service competence of service officers is adequate; 2) The obstacles are: there are service procedures that are not simple and complicated, service facilities are less up-to-date, there are service officers who do not understand information technology, less number of service officers; 3) The efforts to handling the obstacles are simplifying the service procedure with online and offline mechanisms, doing a facilities procurement, holding a training to improve the service officer competence, making a request for additional service officers and utilizing the college students for internships.